Comparing structural soil properties of boreal clay fields under contrasting soil management - Hyväluoma, Jari; Niemi, Petri; Kinnunen, Sami; Brobbey, Kofi; Miettinen, Arttu; Keskinen, Riikka; Soinne, Helena (Wiley-Blackwell, 2024)
Soil management significantly affects soil structure. Tillage and grassland renovation may have destructive influences, while conversion of arable land to grassland can improve pore structure and related soil functions. In crop rotations including perennial grasses, soil structure is affected by these counteracting processes. This work aimed to quantify the impacts of different soil management practices on the structure of boreal clay soils. We studied intact topsoil samples taken from two locations by X-ray computed microtomography, image-based flow simulations and water retention measurements. At both locations, adjacent field areas with two contrasting soil management histories were compared. Both locations had at least a 30-year-old grassland site, which was compared to arable soils either under no-till management with annual crop rotation or conventional tillage with crop rotation including perennial grasses. Both imaging and water retention measurements showed significant differences in the soil macropore structure between the long-term grassland and arable no-till soil such that macroporosity and hydraulic conductivity of the long-term grassland were higher than those of soil under agricultural production. On the contrary, at the second study location, differences between long-term grassland and cultivated fields were minor and the long-term grassland exhibited lower macroporosity. Our results confirm that soil management affects the macropore structure of boreal clay soil and that no-till annual cropping and periodically tilled crop rotation including perennial phases exert different effects on the soil structure as compared with long-term grassland.
Keywords: porosity; soil management; soil structure; water retention; X-ray tomography